Use of Surgisis for Treatment of Anterior and Posterior Vaginal Prolapse - Sara Armitage; Elvis I. Seman; Marc J. N. C. Keirse (Obstetrics and Gynecology International)
Aim. To evaluate the anatomical success and complication rate of Surgisis in the repair of anterior and posterior vaginal wall prolapse. Methods. A retrospective review of 65 consecutive Surgisis prolapse repairs, involving the anterior and/or posterior compartment, performed between 2003 and 2009, including their objective and subjective success rates using the pelvic organ prolapse quantification (POPQ) system. Results. The subjective success rate (no symptoms and no bulge beyond the hymen) was 92%, and the overall objective success rate (no subsequent prolapse in any compartment) was 66% (43 of 65). The overall reoperation rate for de novo and recurrent prolapse was 7.7% with 3 women undergoing repeat surgery at the same site (anterior compartment). No long-term complications occurred. Conclusions. Surgisis has a definite role in the surgical treatment of prolapse. It may decrease recurrences seen with native tissue repair and long-term complications of synthetic mesh. Its use in posterior compartment repair in particular is promising.